Volumetric and Compressibility Behaviour of Some Non-Electrolytes in Aqueous Solutions at 298.15 and 308.15 K - S. Dhondge, Sudhakar; A. Bhalekar, Anil; V. Kaulgud, Murlidhar; R. Tembhurne, Bhimrao (Asian Journal of Chemistry, 2012)
The experiential data for density (r) and speed of sound (u) have been obtained for aqueous solutions of acetonitrile, dimethyl formamide, dimethyl sulphoxide, dioxane, ethylene diamine, ethylene glycol, pyridine and tetrahydro furan at 298.15 and 308.15 K. The data have been processed to compute the derived parameters such as isentropic compressibility of solution (bS), apparent molar volume of solute (fV) and apparent molar isentropic compressibility of solute (fKS). The results obtained have been interpreted in terms of solute-solvent and solute-solute interactions and hydrogen bonding between dissolved solutes and solvent molecules.